“La Minga por el Medio Ambiente: El Proyecto Ambiental Escolar (PRAE) en el Centro Educativo Distrital Arborizadora Alta” (2011)
Este trabajo tenía la finalidad de proporcionar las bases teóricas para la inclusión del Proyecto Ambiental Escolar (PRAE) en el currículo de la Institución Educativa Distrital (IED) Arborizadora Alta, y de estructurar una propuesta metodológica que lleve a la construcción colectiva e interdisciplinar del proyecto. Para ello se elaboró un manuscrito de los conceptos relevantes de la educación ambiental, se conformó el Comité Ambiental Escolar (CAE), y a partir del trabajo colectivo de la comunidad educativa se elaboró un diagnostico ambiental, se determinaron las problemáticas ambientales relevantes del entorno escolar y se procedió a plantear una propuesta de trabajo interdisciplinar para realizar a futuro. / Abstract. In the global meetings on environment defense it is to highlight the role of environmental education, which Colombia is committed to, as a team work between Ministerio Del Medio Ambiente and Ministerio De Educación Nacional. These public bodies propose the project PRAE as a means to change the approach to and attitude towards the environment, and the environmental education as a interdisciplinary tool to boost the values and human skills. The purpose of this job is to settle the theoretical basis that allows the inclusion of the school environmental project in the school syllabus, structuring a methodological proposal to pedagogically work on the communal construction of PRAE. A manuscript of relevant concepts on environmental education was written, it was formed up the School Environmental Committee (CAE, in Spanish), and it was collectively constructed the diagnosis sand determination of the environmental issue. The workshop entitled "Herramientas para la Vida" was developed with teachers, to show the relevance of interdisciplinary work and the inclusion of the environmental education in the institutional syllabus; besides, it worked with CAE children on an analysis guide of the school ground to encourage their work on the environment, and a proposal for interdisciplinary work in the future was made